Common pediatric medical procedures. Venipuncture - Kelleher, Kelly J.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2014)
A complete review and demonstration of the procedure for venipuncture, including vein selection, needle insertion, and blood draw.
Presenter: Kelly J. Kelleher.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Veins -- Puncture; Phlebotomy; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films